Effect of priming in preventing myoclonic movements after intravenous induction with etomidate in adult patients undergoing cardiac surgery: a randomised controlled interventional study - Mukesh K Sunda; Kanchan Chauhan; Rajeev Kumar Prajapati; Krishna Boliwal (Journal of Applied Pharmaceutical Research, 2022)
Etomidate is a hypnotic drug used as an intravenous anaesthetic induction agent. Etomidate causes myoclonic movements in 50-80% patients after induction which makes it less desirable for induction. Aim: Present study was to determine the effect of priming in preventing myoclonic movements after intravenous injection with etomidate in adult patients undergoing cardiac surgery. Materials and Methods: 108 patients ASA grade III scheduled for elective cardiac surgery were allocated randomly in two groups- Group A (n=54): Patients received induction dose of 0.3mg/kg I.V. etomidate, Group B (n=54): Patients received a priming dose of 0.03mg/kg etomidate I.V. followed after 1 minute by induction dose of 0.3 mg/kg I.V. etomidate over 20 seconds. 3 minutes after the start of induction with etomidate, patients in both groups were given injection fentanyl 4mcg/kg followed by injection Rocuronium (1mg/kg bodyweight) to facilitate tracheal intubation. The occurrence and intensity of myoclonus were observed for 3 min from the start of injection of the induction dose and graded clinically by a blinded observer as: 0=no myoclonus, 1=mild myoclonus, 2=moderate myoclonus and 3=severe myoclonus. Result: The average dose of etomidate used during induction and demographic variables were similar in both the groups. The incidence of myoclonus in priming Group (27/54 [50%] was significantly lower than in control Group (45/54 [83.33%].Myoclonus of moderate or severe grade occurred in significantly more patients in control Group (68.3%) than in priming Group (36.5%).Conclusion: Pre-treatment with etomidate (0.03 mg/kg), given 60 seconds before induction of anaesthesia is more effective in reducing the incidence of etomidate-induced myoclonus without related side-effects.